Costly posturing: Relative status, ceremonies and early child development - Xi Chen; Xiaobo Zhang (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
Though social spending facilitates risk-pooling in the impoverished regions, too many resources devoted to social occasions may impose negative externalities and hinder efforts to alleviate poverty for households living close to subsistence. Conducting three waves census-type panel survey in rural western China with well-defined reference groups and detailed information on social occasions, gift exchanges, nutrients intake and health outcomes, we find that the squeeze effect originated from lavish ceremonies is associated with lower height-for-age zscore, higher probability of stunting and underweight in early child development. The lasting impact suggests that 'catch up' is limited. The squeeze is stronger for the fetal period and towards the lower tail of the distribution. Specifically, 39.2%, 33.3% and 64.6% of the sampled households suffer from net squeeze effect on stunting, underweight and lower height-for-age zscore, respectively. The squeeze effect is stronger for 1-3 age cohorts and between 2007 and 2009. We provide suggestive evidence on the intermediate pathways linking social events with poor health outcomes, such as share of food expenditure and basic nutrients intake. Our findings suggest more efficient policy interventions that target the households with pregnant women and of lower social rankings.
Keywords: D13; I32; O15; 330; Relative Status; Squeeze Effect; Nutrients Intake; Stunting; Underweight; Gender